2022
DOI: 10.1038/s42003-022-03432-7
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 enhances Jagged1 mediated NOTCH1 intracellular domain (NICD) deubiquitination and pathological angiogenesis in proliferative retinopathy

Abstract: Pathological retinal neovascularization (NV) is a clinical manifestation of various proliferative retinopathies, and treatment of NV using anti-VEGF therapies is not selective, as it also impairs normal retinal vascular growth and function. Here, we show that genetic deletion or siRNA-mediated downregulation of IL-33 reduces pathological NV in a murine model of oxygen-induced retinopathy (OIR) with no effect on the normal retinal repair. Furthermore, our fluorescent activated cell sorting (FACS) data reveals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…It is mainly expressed in epithelial cells, endothelial cells, and fibroblasts. Studies from our lab and others have shown that IL-33 induces angiogenesis in endothelial cells 20 , 21 . Contrary to it, few reports have also reported that IL-33 attenuates ocular angiogenesis 22 .…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…It is mainly expressed in epithelial cells, endothelial cells, and fibroblasts. Studies from our lab and others have shown that IL-33 induces angiogenesis in endothelial cells 20 , 21 . Contrary to it, few reports have also reported that IL-33 attenuates ocular angiogenesis 22 .…”
Section: Introductionmentioning
confidence: 76%
“…1g ). Our previous study showed that genetic deletion of IL-33 reduces retinal neovascularization in C57BL/6 mice 21 . A study reported significantly higher vitreous levels of vascular cell adhesion molecule (VCAM-1) in patients with proliferative diabetic retinopathy 27 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study showed that IL-33 induced by an oncogenic H-Ras mutant (H-Ras (G12V)) was mainly located in the nuclei of NIH-3T3 cells, and Ras (G12V)-induced cyclin D1 protein synthesis was significantly suppressed by IL-33 knockdown [ 49 ], suggesting a novel role for icIL-33 in cellular transformation. Genetic deletion of IL-33 in retinal endothelial cells reduced pathological retinal neovascularization [ 50 ]. IL-33 enhanced de-ubiquitination and stabilizes the notch1 intracellular domain via interactions with BRCA1-associated protein 1 and Numb in human retinal microvascular endothelial cells, as well as in a murine model of oxygen-induced retinopathy [ 50 ].…”
Section: Nuclear Il-33 Regulates Gene Expressionmentioning
confidence: 99%
“…Genetic deletion of IL-33 in retinal endothelial cells reduced pathological retinal neovascularization [ 50 ]. IL-33 enhanced de-ubiquitination and stabilizes the notch1 intracellular domain via interactions with BRCA1-associated protein 1 and Numb in human retinal microvascular endothelial cells, as well as in a murine model of oxygen-induced retinopathy [ 50 ]. A recent study reported that icIL-33-mediated activation of the Smad signaling pathway in epithelial cells was essential for cancer development during chronic inflammation [ 51 ].…”
Section: Nuclear Il-33 Regulates Gene Expressionmentioning
confidence: 99%